2002
DOI: 10.1136/bmj.325.7376.1332
|View full text |Cite
|
Sign up to set email alerts
|

Fatal toxicity of serotoninergic and other antidepressant drugs: analysis of United Kingdom mortality data

Abstract: Several studies over the past 15 years have compared the number of fatal poisonings due to antidepressant drugs in the United Kingdom with drug use statistics to derive a fatal toxicity index: deaths per million prescriptions.1 2 Greater than 10-fold differences in the index have been shown between tricyclic antidepressants and even larger differences between some tricyclics and newer antidepressants. Explanations have focused on preference for noradrenaline or serotonin reuptake blockade, although only weak c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(95 citation statements)
references
References 5 publications
7
88
0
Order By: Relevance
“…According to several studies VEN has a relatively higher fatal toxicity compared to SSRIs and other newer antidepressants [10,13,16,17,[48][49][50]. Different explanations to this finding have been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several studies VEN has a relatively higher fatal toxicity compared to SSRIs and other newer antidepressants [10,13,16,17,[48][49][50]. Different explanations to this finding have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…VEN has also been shown to have a relatively higher toxicity compared to the SSRIs [10,13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Both indices were significantly greater than that for citalopram, which in turn had a significantly higher mortality index than sertraline. Prior reports, based on comparisons with prescriptions written, have suggested there is greater mortality associated with venlafaxine overdose than with SSRIs (35)(36)(37). Alternatively, Rubino and colleagues (38) found that venlafaxine was more likely to be used in patients who exhibited factors suggesting greater suicidal risk and that adjusting for those factors reduced mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a number of large epidemiological reviews in the UK and Finland have suggested that venlafaxine is associated with more deaths per written prescriptions than other SSRIs suggesting a greater inherent toxicity [3][4][5][6]. It is difficult to determine from these large studies whether this is a true toxic effect or one related to the possibility that venlafaxine is prescribed to patients at higher suicidal risk than those prescribed SSRIs [7].…”
Section: Introductionmentioning
confidence: 99%